EVALUATION OF X, Y, Z GENERATIONS' NUTRITIONAL KNOWLEDGE LEVELS, PREJUDICES AGAINST OBESITY AND THEIR FOOD CHOICES (Third Sector Social Economic Review, 2023)
Objective: To evaluate the nutritional knowledge levels, prejudices against obesity and food choices of X, Y, Z generations.Method: A questionnaire consisting of Nutrition Knowledge Level Scale For Adults (NKLSA), Obesity Prejudice Scale (GAMS-27), Food Choice Questionnaire (FCQ) in order to measure the nutritional knowledge level of the participants with questions about sociodemographic characteristics and eating habits of the participants face to face has been applied. The obtained data were analyzed in SPSS v26 (IBM Inc., Chicago, IL, USA) program.Results: The mean age of the X, Y, and Z generations was 48.92±4.68 years, 34.06±5.14 years, 18.90±1.31 years, and 18.90±1.31 years, respectively; The mean BMI are 27.27±3.25 kg/m2, 26.30±3.69 kg/m2, and 23.01±3.74 kg/m2, respectively. The “GAMS-27 Total” score was found to be statistically higher in generation Y than in other generations (H=14.980; p
Keywords: Obesity bias; food choice; generations; BMI; nutritional knowledge level